Ação do efeito antimicrobiano do laser de diodo de alta potência empregado durante o preparo de canais contaminados com esterococcus faecalis - Santos, Tiago Lange dos (2012)
Endodontic therapy aims to decontaminate root canal systems, as well as the correct sealing and treatment of the dental element. Even with current instrumentation techniques and different types of adjunct irrigating solutions, such as sodium hypochlorite and chlorhexidine, there are obstacles regarding penetration and action on these root canal systems due to their different shapes and resistance of the present pathogens. E. faecalis, bacteria associated with persistent infections of root canal, easily penetrates dentinal tubules. The use of high power diode laser may decrease the incidence of microorganisms that had survived conventional chemical-mechanic preparation. In this study, one hundred and thirty (130) single-rooted human teeth with single canal were used. The samples were filled with E. Faecalis for 14 days and randomly divided in 6 groups: positive control group (CG) without treatment; G NaOC1 2.5%; G NaOCl/L 2.5% + diode laser 3 W; G CHX 2%; G CHX/L 2% + diode laser 3W; and G NaCl + diode laser 3 W. Instrumentation was hybrid with rotary system Protaper and manual files for all groups. After conventional treatment, groups NaOCl/L, CHX/L, and NaCl/L were irradiated. After treating all groups, the persistence of E. faecalis in the interior of the canals was assessed. The group NaOCl had a reduction of 89.82%; the NaOCl/L, 99.42%; G CHX, 81.86%; G CHX/L, 93.48%; and G NaCl, 65.40%. Averages were compared through Anova and complemented by Tukey test at 5% significance. All prepared groups presented significant statistical difference compared to CG, showing statistical difference of G NaCl/L in relation to other groups. There was an improvement in the action of chemical substances when associated to diode laser at 3 W power